Exploring professionals' practices and perspectives on supporting parents with intellectual disabilities: a qualitative study - Rinaldi, Romina; Legierski, Manon; Wauthia, Erika; Mazza, Emma; Batselé, Elise (Frontiers in Rehabilitation Sciences, 2023)
Introduction: Evidence suggests that parents with intellectual disabilities require appropriate parenting support. However, professional practices vary widely, and several barriers and challenges persist in supporting parents with intellectual disabilities. To identify effective and collaborative practices, this study investigated practices reported by professionals and their roles in providing services to parents with intellectual disabilities. Methods: Semi-structured interviews were conducted with 22 professionals from three sectors (disability, early childhood, and healthcare), and the content was analysed using inductive thematic analysis. Results: Thematic analyses yielded four main themes: (1) Perceived professional practices, (2) professional stances, (3) the frame of reference and the ethics of support, (4) the experience of providing support. They are described in terms of content and distribution across sectors to provide an overview of practices as well as potential discrepancies. Conclusions: This study concludes by developing recommendations on good practices for support professionals to respond as adequately as possible to meet the needs of parents and future parents with intellectual disabilities, which include structural support and guidelines for professionals to provide sensitive, family-centred, and enabling support.